Global threats from invasive alien species in the twenty-first century and national response capacities - Regan Early (Nature Portfolio, 2016)
Globalization facilitates the spread of invasive alien species, while environmental change can ease invasion. Here, Early et al. identify vulnerable regions globally and evaluate capacity in vulnerable countries to prevent invasions arising from sources such as air travel, horticulture, and pet trade.